The murder list - Ryan, Hank Phillippi (Forge, 2019)
Law student Rachel North is the ultimate reliable narrator--she will tell you, without hesitation, what she knows to be true. She's smart, she's a hard worker, she does the right thing. She's successfully married to a faithful and devoted husband, a lion of Boston's defense bar. And her internship with the powerful District Attorney's office is her ticket to a successful future. Problem is--she's wrong. Rachel. Jack. Martha. Who is next on The Murder List? And in this cat and mouse game--the battle for justice becomes a battle for survival. The Murder List is a new standalone suspense novel in the tradition of Lisa Scottoline and B. A. Paris from award-winning author and reporter Hank Phillippi Ryan.